2018
DOI: 10.21475/ajcs.18.12.10.p1129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interrelationship among tepary bean (Phaseolus acutifolius A. Gray) genotypes revealed through SSR markers

Abstract: Tepary bean (Phaseolus acutifolius A. Gray) is one of the useful plant genetic resources possessing novel genes for abiotic and biotic stress tolerance. It is largely used in the breeding of common bean or related tropical legumes. The objective of this study was to determine the genetic interrelationship present among 20 diverse tepary bean genotypes using 10 selected and polymorphic simple sequence repeat (SSR) markers and to identify genetically unique parental lines for developing breeding populations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Also, tepary bean can be readily crossed with its wild relatives (Blair et al, 2003), which is useful to create genetic variation for development and advancement of families possessing key agronomic and physiological traits that improve yield gains under constrained environments. Though limited genetic divergence is reported among domesticated tepary bean genetic pool, genotypic differences exist for agronomic (Bhardwaj, Rangappa, & Hamama, 2002; Federici, Ehdaie, & Waines, 1990; Mhlaba, Amelework, Shimelis, Modi, & Mashilo, 2018a; Mohamed, Mohamed, Schmitz‐Eiberger, Keutgen, & Noga, 2005), physiological and biochemical (Mohamed et al, 2005; Türkan, Bor, Özdemir, & Koca, 2005) traits. This variation for key traits is useful and provides opportunities for strategic crossing of promising and complementary genotypes to increase favourable alleles for key agronomic, physiological and biochemical traits to improve drought adaptation and yield gains.…”
Section: Tepary Bean Genetic Resources For Drought Adaptation Breedingmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, tepary bean can be readily crossed with its wild relatives (Blair et al, 2003), which is useful to create genetic variation for development and advancement of families possessing key agronomic and physiological traits that improve yield gains under constrained environments. Though limited genetic divergence is reported among domesticated tepary bean genetic pool, genotypic differences exist for agronomic (Bhardwaj, Rangappa, & Hamama, 2002; Federici, Ehdaie, & Waines, 1990; Mhlaba, Amelework, Shimelis, Modi, & Mashilo, 2018a; Mohamed, Mohamed, Schmitz‐Eiberger, Keutgen, & Noga, 2005), physiological and biochemical (Mohamed et al, 2005; Türkan, Bor, Özdemir, & Koca, 2005) traits. This variation for key traits is useful and provides opportunities for strategic crossing of promising and complementary genotypes to increase favourable alleles for key agronomic, physiological and biochemical traits to improve drought adaptation and yield gains.…”
Section: Tepary Bean Genetic Resources For Drought Adaptation Breedingmentioning
confidence: 99%
“…In tepary bean, seed yield is positively associated with NPPP and HSW under water‐limited condition (Kuruvadi & Valdez, 1993) and harvest index under non‐stressed condition (Mhlaba et al, 2018a). NSPP, NPPP, and HSW exhibit high BSH (>80) under drought stress conditions (Kuruvadi & Valdez, 1993).…”
Section: Agronomic Traits Associated With Drought Tolerance and Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Tepary bean shows wide genetic and morphological variation [16][17][18], with yield gains that can be above 2000 kg per hectare [19]. For example, Mhlaba et al [20] and Blair et al [21] revealed high genetic diversity in tepary bean using simple sequence repeats (SSR) markers. The genetic variability offers opportunities for cultivar development with the farmer and market-preferred desired traits.…”
Section: Introductionmentioning
confidence: 99%